Pengembangan Bahan Ajar Canva dalam Meningkatkan Semangat Belajar Peserta Didik pada Materi Hidangan Tradisional Indonesia - Sherly Yanuarendra Lova; Agus Ridwan Misbahuddin; Nur Badriyah; Rahmah Izza Safira; Revo Firmansyah (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
The advancement of digital technology has significantly transformed the education sector, including vocational learning, especially in the culinary field. However, based on initial observations at SMK YPM 2 Taman, the learning process still tends to rely on printed information sources such as books and Student Worksheets. This research aims to develop learning materials using Canva as a way to motivate students in their learning. The approach used in this study is Research and Development (R&D) with the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The validation results from experts indicate that the developed learning materials are categorized as "Valid," with a validity rate of 85.6% for the media aspect and 86.3% for the content aspect. Furthermore, the comparison of pretest and posttest results shows an increase in students' understanding and learning motivation, although 25% of students have not yet reached the learning completeness standard. Therefore, learning materials using Canva have proven to be effective in enhancing students' learning motivation and academic achievement and can be used as a more innovative and interactive learning tool.